Types of Writing Strategies Used by EFL Students with High Achievement in Writing Undergraduate Thesis - Iqlima, Putri Amifalahiya; Panggabean, Christina Innocenti Tumiar (Universitas Pendidikan Mandalika, 2025)
One of the most difficult skills in English is writing, especially for university students who have to master academic writing because they have final project in writing undergraduate thesis. The students face many difficulties in writing undergraduate thesis because they need to learn how to communicate the argument rationally and provide evidence in intellectual perspective to present the arguments in a logical order. In order to solve their writing problems, students can apply writing strategies. Therefore, this study is about writing strategies used by EFL students in undergraduate thesis writing process at English Education study program. This study’s objectives are to find out the kinds of writing strategies, and the dominant writing strategy applied by EFL students in writing undergraduate thesis. This research employed descriptive qualitative procedure with case study design. The subjects of the study were eleven EFL students of 2019 class at UNIROW. The data were taken from the questionnaire and interview. Then, the data were analyzed qualitatively through data reduction by identifying, grouping and coding, data display, describing, interpreting, and conclusion drawing. The result showed that the students applied 8 strategies in before writing, 14 strategies in during writing, and 16 strategies in after writing. The dominant strategy applied was during writing with the average score of 3.68, which can be categorized as high frequency, followed by before writing (3.54), and after writing (3.23). In conclusion, writing strategies are essential in assisting students during writing undergraduate thesis to produce better academic writing.